IMPLEMENTATION OF THE PALAPA MOJO APPLICATION ON SITI PINTER FEATURES IN IMPROVING EDUCATION IN MOJOKERTO CITY - Laili, Safitri Nur; Suryadi, S; Muluk, Mujibur Rahman Khairul (Erudio Journal of Educational Innovation, 2024)
The application of information and communication technology (ICT) in public services and education has become a main focus for many city governments in this digital era. Mojokerto City is no exception, introducing innovation through the Palapa Mojo application. This application integrates various government services into one platform, with a feature that aims to enhance education for the people of Mojokerto City, namely Siti Pinter, which provides technology training for the public. This study investigates the implementation of Palapa Mojo and the factors influencing its development in Mojokerto City. A case study method is used to gain a deep understanding of the implementation process and the associated inhibiting factors. Data is collected through interviews, observations, and document analysis. The research results show that Palapa Mojo has successfully increased the efficiency of public services, improved digital literacy, and provided wider educational access through the Siti Pinter platform. This application, which includes key features like Siti Pinter, is designed to enhance the public's digital literacy and technological skills. Despite receiving positive responses from the community, the development of this application faces various obstacles. Internal inhibiting factors include the lack of policy integration for the application and low commitment from organizational units (OPD). External inhibiting factors include dependency on third parties for application development, difficulties in integrating with central government systems, and low digital literacy among the population. To overcome these obstacles, clear policies and regulations, strong commitment from all OPDs, and enhanced coordination with the central government are necessary. Additionally, intensive socialization, education, and training efforts must be undertaken to increase the digital literacy of the population. With this approach, it is expected that the Palapa Mojo application can provide maximum benefits, improve the quality of public services, and strengthen the technological capabilities of the people of Mojokerto City.